1989
DOI: 10.1073/pnas.86.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of FLA, the cat major histocompatibility complex.

Abstract: The major histocompatibility complex (MHC) of the domestic cat (termed FLA) has been refractile to genetic and serological definition largely because of repeated failure to detect cytotoxic antibodies in multiparous cats or to elicit antibody following allogeneic lymphocyte immunization. We have developed a protocol for producing cytotoxic alloantisera in the cat following rejection of multiple surgical skin grafts. Of 59 cats subjected to grafting, 13 produced lymphocytotoxic antisera which had varying specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The first species group included mouse and human, species with abundant functional MHC variability (12). The second group comprised 16 random-source domestic cats (Felis catus), a species that displays antigenic diversity at the MHC, termed FLA, but less than that observed in mouse or man (25). The third group included two populations of African cheetah subspecies, A. jubatus jubatus (South African) and A. jubatus raineyi (East African).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first species group included mouse and human, species with abundant functional MHC variability (12). The second group comprised 16 random-source domestic cats (Felis catus), a species that displays antigenic diversity at the MHC, termed FLA, but less than that observed in mouse or man (25). The third group included two populations of African cheetah subspecies, A. jubatus jubatus (South African) and A. jubatus raineyi (East African).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, species that have abundant MHC antigenic variability (mouse, pig, rat, and mole rat) show appreciable DNA variation. The domestic cat, which has an intermediate level of functional MHC polymorphism (25) After transfer, nitrocellulose filters were hybridized with MHC class I molecular clones derived from homologous species, i.e., 5'Db for mouse (21), HLAB7 for human (22), and pFLA24 for cat and cheetah (23). Cheetah diversity than 10 species of felids or other mammals similarly typed with 50 allozyme markers (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…2, 3). Loss of the DQ and DP genes may be the reason for a remarkable immunological "tolerance" seen in cats from several perspectives, including: (1) the lack of cytotoxic antibody production (including IgE) in multiparous cats (Pollack et al 1982;Winkler et al 1989), (2) very inefficient antibody induction; only 13 of 59 domestic cats (22%) produced detectable levels of antibodies following allogenic lymphocyte immunization and skin graft transplantation (Winkler et al 1989), and (3) a remarkable tolerance for allogenic bone marrow and tissue transplants among noninbred cats used in gene therapy protocols (Simonaro et al 1999;Sun et al 1999). The critical role of class II gene families in antibody production would support the notion that DP/DQ loss in domestic cats contributes to quantitative diminution of antibody recognition and induction.…”
Section: Discussionmentioning
confidence: 99%
“…Winkler et al [20] have reported that skin-grafts transplanted between unrelated cats could not survive longer than 10 days. The cats used in the present study were all unrelated, so that we considered that the duration of skin-allograft survival might be prolonged by matching the types of DRB subgroups with the RT-PCR-RFLP method.…”
Section: Discussionmentioning
confidence: 99%